Batasan Penggunaan Artificial Intellegence (AI) dalam Pembuatan Akta Notaris di Indonesia - Ahmad Reysa Fateya Rahman; Nadyatul Jannah; Muhammad Ikhlas; Muhammad Arifin Ilham; Ahmad Firza Agustiawan (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The implementation of Artificial Intelligence (AI) in drafting legal documents has become an imminent phenomenon in the Society 5.0 era, including within Indonesian notarial practices. Although it promises administrative efficiency and enhanced accuracy, adopting this technology without clear boundaries poses a substantial risk to legal certainty. This study aims to analyze the legal standing of AI in deed-making processes, examine its operational boundaries concerning notarial authority, and assess its juridical implications on the validity of authentic deeds under Indonesian positive law. Utilizing a normative legal research method with statutory and conceptual approaches, secondary data were qualitatively analyzed through deductive reasoning. The results indicate that AI is not recognized as a legal subject; instead, its capacity is strictly limited to an administrative support tool during the pre-drafting stage (formulation stage). Its application is rigidly constrained by Article 16, Paragraph (1), Letter m of the Notary Jougnal Act (UUJN), which absolutely mandates the physical presence of all parties during the reading and signing of the deed. Furthermore, AI lacks the moral conscience required to evaluate legal capacity (rechtsbekwaamheid) and detect defects of consent among appearers. Consequently, the principle of personal liability remains fully attached to the notary. Negligence in supervising AI outputs or breaching professional secrecy via unencrypted third-party platforms can render the resulting deed legally flawed, voidable, or void ab initio.